Studies in maritime economics - Goss, R. O. (London: Cambridge U.P., 1968)
This book is a collection of papers, with the general theme of efficiency in sea transport. These essays embrace seaports and the activities of ships in seaports as well as the ships themselves.
Bibliographical footnotes.
ne 6/03/2018
loans
Keywords: Shipping; Maritime economics